1996
DOI: 10.1002/(sici)1098-1136(199602)16:2<174::aid-glia9>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Induction of astroglial gene expression by experimental seizures in the rat: Spatio‐temporal patterns of the early stages

Abstract: The levels of glial fibrillary acidic protein mRNA were analysed by in situ hybridization during the first 6 h in experimental models of status epilepticus in the rat. Two different models of status epilepticus were studied: one is produced by the administration of pilocarpine to lithium-treated rats and the other by the intracerebroventricular administration of kainate. Results obtained in the present study showed a very rapid (as early as 1.5 h in periventricular zones of hypothalamus, cerebral cortex, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This glial hypertrophy was observed in the light microscopic preparations and was also shown convincingly in electron microscopic images obtained from the hilus at all of the time points examined. The appearance of hypertrophied processes with large bundles of glial filaments as early as one day after seizures would presumably be preceded by increased GFAP mRNA, which can be seen in some regions of the hippocampus as early as 1.5 hrs after pilocarpine‐induced seizures (Belluardo et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This glial hypertrophy was observed in the light microscopic preparations and was also shown convincingly in electron microscopic images obtained from the hilus at all of the time points examined. The appearance of hypertrophied processes with large bundles of glial filaments as early as one day after seizures would presumably be preceded by increased GFAP mRNA, which can be seen in some regions of the hippocampus as early as 1.5 hrs after pilocarpine‐induced seizures (Belluardo et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies strongly suggested a role for inflammation in the pathogenesis of epilepsy. Rapid glial activation has been observed in the adult and immature brain following seizure activity (Khurgel et al., 1995; Belluardo et al., 1996; Taniwaki et al., 1996; Vezzani et al., 2002; Rizzi et al., 2003; Ravizza et al., 2005). Cytokine neosynthesis is induced by seizure in an age‐dependent manner (Rizzi et al., 2003; Ravizza et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Both the time course of the phenomenon and the localization of Cx43‐ and Cx32‐expressing cells suggest the possible involvement of reactive glial cells. Indeed, the well‐know localization of Cx43 in astrocytes and the similarity of spatio‐temporal expression patterns of Cx43 mRNA with those of GFAP mRNA (Belluardo et al ., 1996) are in favour of a role of reactive astrocytes. The up‐regulation of Cx43 in reactive astrocytes has been previously reported in other brain injury models (Theriault et al ., 1997; Rami et al ., 2001), and in temporal cortex of patients exhibiting seizures disorders (Naus et al ., 1991).…”
Section: Discussionmentioning
confidence: 99%